(3ZGjI GdSDGd aj NUGFU GdQShds - (3YeQ Hf Ydj Hf CMeO GdCfUGQj GdTGaYj, SQGL GdOjf, CHh MaU GHf GdfMhj, GdeYQha HGHf Gdedbf, J (B804 (3g` s
(3ChdgG (B:s
(3hHYO agPG eNJUQ fGaY Ef TGA Gddg JYGdi ajeG jJYdb HNUGFU CTQa GdeNdhbjf hCaVd GdSGHbjf hGdGMbjf Udi Gddg Ydjg hYdi SGFQ GdfHjjf hGdeRfi QVi Gddg Yfg EaJJM cJGH GdfcGM HgG s
(3BNQgG (B:s
(3jfJgi HGdNGUjI GdSGOSI hGdKdGKjf (B( (3ef QBg ai GdefGe abO QBg MbkG aEf GdTjWGf dGjJeKd ai UhQJg Udi Gddg Ydjg hSde (B) s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hbO CcedJ ef fSNI CNQi Qbe (B3365 (3HecI NOGHNT HJfg cJHJ SfI (B1085(3g` s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B57s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1192s
Keywords: (3CUhd Gdabgs